(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2025)
This section contains the works presented at the XIV Regional Catalysis Meeting, which took place in Campinas in May 2024. With the general theme "From bench to industry: the challenges of Catalysis", the event outlined 92 works distributed on its eight thematic areas.